2014
DOI: 10.1002/embr.201338080
|View full text |Cite
|
Sign up to set email alerts
|

Polo‐like kinase‐1 triggers histone phosphorylation by Haspin in mitosis

Abstract: Histone modifications coordinate the chromatin localization of key regulatory factors in mitosis. For example, mitotic phosphorylation of Histone H3 threonine-3 (H3T3ph) by Haspin creates a binding site for the chromosomal passenger complex (CPC). However, how these histone modifications are spatiotemporally controlled during the cell cycle is unclear. Here we show that Plk1 binds to Haspin in a Cdk1-phosphorylation-dependent manner. Reducing Plk1 activity decreases the phosphorylation of Haspin and inhibits H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 46 publications
5
73
0
1
Order By: Relevance
“…PLK1 is overexpressed in many human tumors and is associated with tumorigenesis (15). It has been recently reported that PLK1 phosphorylates the N terminus of Haspin, leading to its activation and resulting in the phosphorylation of the threonine 3 on histone H3 tail (H3T3) (16,17). Then H3pT3 is recognized by the chromosome passenger complex, resulting in cluster-mediated autophosphorylation and autoactivation of Aurora B (18,19).…”
mentioning
confidence: 99%
“…PLK1 is overexpressed in many human tumors and is associated with tumorigenesis (15). It has been recently reported that PLK1 phosphorylates the N terminus of Haspin, leading to its activation and resulting in the phosphorylation of the threonine 3 on histone H3 tail (H3T3) (16,17). Then H3pT3 is recognized by the chromosome passenger complex, resulting in cluster-mediated autophosphorylation and autoactivation of Aurora B (18,19).…”
mentioning
confidence: 99%
“…The CSN is a kinase phosphatase signaling network that contains four kinases: Aurora B kinase, which is part of the CPC, MPS1 kinase, Bub1 kinase and Haspin kinase, as well as Sgo1, which binds Protein Phosphatase 2a (PP2A). Plk1 kinase is also involved [1,2,3,4], however we have limited our discussion of Plk1 because its kinetochore functions are poorly understood. One major reason to explore the concept that the CSN proteins coordinate mitotic events is that sets of CSN proteins regulate different events in mitosis (Figure 2).…”
Section: Are Mitotic Events Coordinated?mentioning
confidence: 99%
“…This auto-inhibition is released through Cdk1 phosphorylation of Haspin N-terminus followed by the recruitment of Plk1 on the Cdk1 phospho-site and its activation. Activated Plk1 phosphorylates several sites on Haspin N-terminus releasing its activity in a timely manner at the beginning of mitosis triggering H3T3 phosphorylation and CPC recruitment at centromeres [47,48]. Furthermore, Wang et al showed that Aurora B further phosphorylates Haspin Nterminus enhancing its ability to generate H3T3 phospho-sites for Survivin/CPC binding [49] ( Figure 5 lower panel).…”
Section: Regulation Of Haspin Activitymentioning
confidence: 99%
“…Haspin phosphorylation by Cdk1/cyclin B starts on T128 of human Haspin (T206 in Xenopus laevis) [47,48]. Gheniou et al showed that Xenopus Haspin auto-inhibits itself during interphase through a conserved basic site in its N-terminus part close to its kinase domain [47].…”
Section: Regulation Of Haspin Activitymentioning
confidence: 99%